2021
DOI: 10.1097/mlr.0000000000001563
|View full text |Cite
|
Sign up to set email alerts
|

How Should We Organize Care for Patients With Human Immunodeficiency Virus and Comorbidities? A Multisite Qualitative Study of Human Immunodeficiency Virus Care in the United States Department of Veterans Affairs

Abstract: Supplemental Digital Content is available in the text.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 20 publications
1
3
0
Order By: Relevance
“…Similarly, we found clinician participants wanted increased transparency in "ownership" of clinical activities when care is shared between multiple clinicians. Analogous results have been identified by another study conducted among multiple Department of Veterans Affairs Medical Centers; the authors of that study found that for team-based care to be effective, there must be coordination of services [17].…”
Section: Discussionsupporting
confidence: 69%
See 1 more Smart Citation
“…Similarly, we found clinician participants wanted increased transparency in "ownership" of clinical activities when care is shared between multiple clinicians. Analogous results have been identified by another study conducted among multiple Department of Veterans Affairs Medical Centers; the authors of that study found that for team-based care to be effective, there must be coordination of services [17].…”
Section: Discussionsupporting
confidence: 69%
“…In this transitional period, it is useful to understand patient and clinician preferences for care as well as perceived solutions to care improvement. This is particularly the case for patients struggling to effectively manage their conditions, yet few studies have sought to examine this; those that have, have largely focused on self-management strategies as opposed to care delivery [14][15][16][17].…”
Section: Introductionmentioning
confidence: 99%
“…Our data indicated that patients felt supported by IHWC providers in working toward their health goals. As team-based interdisciplinary care is the standard model in the VA for primary and some specialty care (e.g., HIV, chronic pain care), 30 - 34 our findings suggest that interdisciplinary integrative health clinics could be used to help guide patients toward evidence-based and best-practice use of CIH and Whole Health resources in VA. Our findings also indicate the potential effectiveness of such a model to support patients’ holistic health and wellness goals.…”
Section: Discussionmentioning
confidence: 85%
“…Primary care services may be provided by HIV primary care providers, by generalist primary care providers, or through shared care wherein a HIV subspecialist and a primary care provider collaboratively manage Veterans' primary care needs (Fix et al, 2014). Studies examining differences in cardiovascular disease preventative care in the VHA have not identified a superior care model (Bokhour et al, 2021). Yet, there is a demonstrated need for enhanced cardiovascular disease prevention efforts in people with HIV, particularly for Veterans from underrepresented racial and ethnic groups (Richardson et al, 2016).…”
Section: Enhancing Cardiovascular Disease Prevention In Veterans With...mentioning
confidence: 99%